Long-Term Effects of Pre-Placement Risk Factors on Children's Psychological Symptoms and Parenting Stress Among Families Adopting Children From Foster Care. (June 2017) - Nadeem, Erum; Waterman, Jill; Foster, Jared; Paczkowski, Emilie; Belin, Thomas R.; Miranda, Jeanne
This exploratory longitudinal study examined behavioral outcomes and parenting stress among families with children adopted from foster care, taking into account environmental and biological risk factors. Child internalizing and externalizing problems and parenting stress were assessed in 82 adopted children and their families at 2 months post-placement, 12 months post-placement, and then yearly until 5 years post-placement. A history of abuse/neglect predicted significantly higher externalizing and internalizing problems at a borderline level of statistical significance. In the initial stages after placement, externalizing problems were significantly higher among children who were 4 years or older at placement versus those who were younger than 4, although differences were no longer significant 5 years post-placement. Statistical trends in parenting stress reflected reduced stress in the first 12 months followed by a plateau for parents who adopted older children and greater stress for parents who adopted younger children. Familiar limitations for observational cohort data apply. Nonetheless, the availability of longitudinal follow-up on a sizable sample of children adopted from foster care adds insight to the psychological dynamics for adoptive families and suggests that families of children adopted from the foster care system may have unique needs for ongoing support around behavioral issues.